(untitled) (Research, Society and Development, 2022)
The manufacture and characterization of gluten-free pasta based on black rice flour by-products from the industrial processing of black rice grains were addressed in this study. The black rice pasta (BRP) was extruded in a penne format developed with black rice flour: white rice flour 1:2 w/w, and the addition of food additives to improve the texture and viscoelasticity proprieties of pasta: tapioca starch, xanthan gum, egg, and water. The cooking quality, texture parameters, CIEL*a*b* color, and total monomeric anthocyanin (TAM) content were evaluated. The optimum cooking time was adjusted to 7 minutes, BRP presented 31.9% of moisture, water absorption of 68.0%, and cooking loss of 4.8%. Texture properties of BRP were positively affected by the presence of additives and presented firmness and adhesiveness values of 2.54 N and 0.01 N, respectively. Cooked BRP presented 10.4 mg of cyanidin-3-glycoside / 100 g (dry basis), carrying a reduction of only 16% of the TAM content related to the dough before cooking. Sensory analysis performed with 100 untrained testers showed high acceptance indexes (between 67% and 89%), with flavor and texture the most well-evaluated attributes contributing to an expressive purchase intention (86%) if the product was available for sale. It was possible to reuse a residue from black rice-processing and develop an innovative, high-quality gluten-free pasta, with a peculiar chestnut flavor, a natural purple color, with nutritional properties, antioxidants and being gluten-free, it is a product with potential to benefit and increases the diversity of food for celiac patients.